World History - Ellis, Elisabeth Gaynor; Esler, Anthony (Boston : Pearson prentice Hall, 2009)
Art, Culture and History
2011-10-30
Keywords: World History; Civilization; Ancient Egypt; Ancient Greece; American Civilization; Muslim Civilization; French Revolution; Industrial Revolution; Imperialism; World War; Cold War